ANALISIS KELAYAKAN USAHA BAGLOG JAMUR TIRAM ALBASIA KELOMPOK DISABILITAS REJO MANDIRI DI DESA SIDOREJO, PURWOREJO - Gelis Ariani; Isna Windani; Uswatun Hasanah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
This study aims to: (1) describe the production process, (2) analyze the costs, revenue, income, and profit, and (3) assess the feasibility of the oyster mushroom baglog business made from Albizia chinensis sawdust managed by the Disability Group “Rejo Mandiri” in Sidorejo Village, Purworejo District, Purworejo Regency. The research employed a case study method with a quantitative descriptive approach. Primary data were obtained through observation, interviews, and cost recording, supported by secondary data from relevant literature and institutional reports.The business feasibility analysis was conducted from October 2024 to May 2025 using technical and financial indicators. The production costs during the study period were IDR 1,676,000; IDR 475,300; IDR 608,000; and IDR 795,000, respectively. The incomes obtained were IDR 2,660,000; IDR 308,000; IDR 560,000; and IDR 860,000. The calculated R/C ratios were 1.70, 1.05, 1.23, and 1.32, while the Break Even Point (BEP) production levels were 75, 136, 104, and 99 baglogs, respectively. The results indicate that the oyster mushroom baglog business generates positive income and profit. The R/C ratio values greater than one in each production period, as well as the actual production and selling price exceeding the break-even point, indicate that the business is financially feasible and has potential for further development.